Pervasive systemic disparities: medical-related gaslighting, trauma, and distrust among LGBTQ+ people in the United States - Nowaskie, Dustin Z.; Blackwood, Dehandra; Garcia, Frank (Frontiers in Sociology, 2025)
IntroductionHistorically, LGBTQ+ people have and continue to endure discrimination across many contexts, including healthcare. Research and data from nationwide samples in the United States regarding medical-related stigma experienced by LGBTQ+ people are scant.MethodsA cross-sectional survey was distributed online to a national sample of United States residents. Participants answered questions about their healthcare, including experiences with medical-related gaslighting, trauma, and trust.ResultsCompared to cisgender and heterosexual people (n = 857), LGBTQ+ people (n = 815) reported significantly higher rates of medical-related gaslighting (46.5% vs. 26.5%, ORs 1.75–2.80) and trauma (18% vs. 8.9%, ORs 1.63–2.66). Likewise, LGBTQ+ people conveyed significantly less trust (ORs 0.46–0.53) in primary care providers (59.8% vs. 74.1%), medical specialists (56.5% vs. 71.7%), pharmaceutical companies (17% vs. 28%), insurance companies (15.9% vs. 29.3%), and U.S. healthcare systems (17.8% vs. 30.4%).DiscussionMedical-related gaslighting, trauma, and distrust are pervasive systemic disparities among LGBTQ+ people. Addressing these challenges will require ongoing, lifelong motivation, dedication, and commitment for LGBTQ+ education, advocacy, and leadership to dismantle current prejudiced practices and foster more inclusive, supportive, affirming healthcare environments.